Combined Upper Limb Exercise and Creatine Monohydrate Supplementation Improved Musculoskeletal Function in NSCLC Patients - Muhammad Addinul Huda; Ana Rima Setijadi; Reviono Reviono; Farih Raharjo; Yusup Subagio Sutanto (Jurnal Respirologi Indonesia, 2022)
Background: Lung cancer is a chronic respiratory disease that causes muscle dysfunction. Giving creatine monohydrate supplementation combined with exercise has efficacy in increasing lean body mass (LBM), muscle strength, and physical function. This study aims to analyze the effect of a combination of creatine monohydrate supplementation and upper limb exercise on skeletal muscle dysfunction in NSCLC patients.Methods: A quasi-experimental study with a pretest-posttest study on NSCLC patients given epidermal growth factor receptor (EGFR) – tyrosine kinase inhibitors (TKIs) from outpatient at RSUD Dr. Moewardi Surakarta in September - October 2021. The combination group of creatine monohydrate supplementation with upper limb exercise (n=15), the group with creatine monohydrate supplementation only (n=16), and the control group (n=15). Lean body mass in kilograms and percentages, 6-minute walk test (6MWT), and quality of life were assessed after 8 weeks of treatment.Results: The increase in LBM in the combination group was 4.22±1.81kg and 6.38±2.48% (P=0.0001). The combination groups have a greater increase in the 6MWT was 104±20.07 meters. The increase in quality of life in the combined creatine monohydrate supplementation group with upper limb exercise was 20.80±10.75. Changes in the value of LBM, 6MWT, and quality of life (QoL) in the creatine monohydrate supplementation combined with upper limb exercise were significantly different compared to the creatine monohydrate supplementation only group and the control groups.Conclusion: There is a greater effect of giving a combination of creatine monohydrate supplementation and upper limb exercise on LBM, 6MWT, and QoL in NSCLC patients.